David Copperfield [videorecording (DVD)] - Fields, W. C. (William Claude), 1880-1946; Barrymore, Lionel, 1878-1954; O'Sullivan, Maureen, 1911-1998 ([Publisher not identified], 2013)
Dickens' classic story about an orphaned boy who, with the help of a kindly aunt, escapes his stepfather's cruelty and grows up to become a successful author.